The draft genome of the C3 panicoid grass species Dichanthelium oligosanthes. Issue 1 (December 2016) - Studer, Anthony; Schnable, James; Weissmann, Sarit; Kolbe, Allison; McKain, Michael; Shao, Ying; Cousins, Asaph; Kellogg, Elizabeth; Brutnell, Thomas
Abstract Background Comparisons between C3 and C4 grasses often utilize C3 species from the subfamilies Ehrhartoideae or Pooideae and C4 species from the subfamily Panicoideae, two clades that diverged over 50 million years ago. The divergence of the C3 panicoid grassDichanthelium oligosanthes from the independent C4 lineages represented bySetaria viridis andSorghum bicolor occurred approximately 15 million years ago, which is significantly more recent than members of the Bambusoideae, Ehrhartoideae, and Pooideae subfamilies.D. oligosanthes is ideally placed within the panicoid clade for comparative studies of C3 and C4 grasses. Results We report the assembly of the nuclear and chloroplast genomes ofD. oligosanthes, from high-throughput short read sequencing data and a comparative transcriptomics analysis of the developing leaf ofD. oligosanthes, S. viridis, andS. bicolor . Physiological and anatomical characterizations verified thatD. oligosanthes utilizes the C3 pathway for carbon fixation and lacks Kranz anatomy. Expression profiles of transcription factors along developing leaves ofD. oligosanthes andS. viridis were compared with previously published data fromS. bicolor, Zea mays, andOryza sativa to identify a small suite of transcription factors that likely acquired functions specifically related to C4 photosynthesis. Conclusions The phylogenetic location ofD. oligosanthes makes it an ideal C3 plant for comparative analysis of C4 evolution in the panicoid grasses. This genome will not only provide a better C3 species for comparisons with C4 panicoid grasses, but also highlights the power of using high-throughput sequencing to address questions in evolutionary biology.